2006
DOI: 10.1186/1471-244x-6-58
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in cognitive and psychosocial functioning and self image among adolescent inpatient suicide attempters

Abstract: Background: Psychiatric treatment of suicidal youths is often difficult and non-compliance in treatment is a significant problem. This prospective study compared characteristics and changes in cognitive functioning, self image and psychosocial functioning among 13 to 18 year-old adolescent psychiatric inpatients with suicide attempts (n = 16) and with no suicidality (n = 39)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Therefore, a mindful approach towards self-image is highly recommended (Maltz, 1960, Proctor, 2002. Improvement in self-image as a result of receiving an intervention is in line with previous studies conducted by Hintikka et al (2006) and Ryum, Vogel, Walderhaug, and Stiles (2015) in which participants'/patients' levels of self-image improved significantly, almost to that of a normal person, after undergoing the treatments.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, a mindful approach towards self-image is highly recommended (Maltz, 1960, Proctor, 2002. Improvement in self-image as a result of receiving an intervention is in line with previous studies conducted by Hintikka et al (2006) and Ryum, Vogel, Walderhaug, and Stiles (2015) in which participants'/patients' levels of self-image improved significantly, almost to that of a normal person, after undergoing the treatments.…”
Section: Discussionsupporting
confidence: 89%
“…Tonge et al (2008) mention that adolescents are more conscious of problems in their families than their parents are, and that this was an area of concern to them. Hintikka et al (2006) recommend that family sessions should be included in a therapy programme for adolescents as it would assist with their rehabilitation.…”
Section: Discussionmentioning
confidence: 98%
“…in adolescents suffering from anorexia or bulimia, suicidal adolescents, or adolescents in migrating populations. [35][36][37][38][39][40][41][42][43][44] Studies using the Youth Self Report, SDQ, YEDE-Q, EES-C and SRQ-20 reported overweight male and female adolescents as having psychopathological symptoms, suffering more from mental disorders, and reporting body dissatisfaction and problems in psychosocial functioning. [45][46][47][48][49] The inadequate adjustment in sexual attitudes revealed by the overweight adolescent girls in our study could be a result of dissatisfaction with their bodies, resulting in feelings of unattractiveness in comparison with the cultural 'standards' imposed by Western society.…”
Section: Discussionmentioning
confidence: 99%